A társadalmi egyenlőtlenségek növekedése a rendszerváltás óta - Andorka, Rudolf (Szociológiai Szemle, 2024)
Based on the data from the four waves from 1992 to 1995 of the Hungarian Household Panel Survey the growth of inequalities and of poverty by social strata, residence, ethnicity age, etc. is presented. The traditional income inequalities, with managers at the top and non-skilled workers and peasants at the bottom, increased since the system change. The incodence of poverty also increased and is highly differentiated by social and demographic categories. In addition to the „tradition poor”, the ninskilled workers and peasants and the residents of villages, new or hitherto less observed groups of poverty are visible: the children, the unemployed and adult dependants and - last but first - the persons belonging the the roma ethnic group. The members of the poorer social strata are more dissatisfied, suffer more mental health problems and show more often signy of anomie and alienation.